Interesting Applications of Mobile Robotic Motion by using Control Algorithms - Mustafa, Syed Khalid; Kopot, M.; Ahmad, M. Ayaz; Lyubchenko, V.; Lyashenko, V. (WARSE, 2020)
Robots are widely used in various fields of production. These complex technical devices are able to facilitate the work of man. Among the varieties of robots, it is necessary to highlight mobile robots. The ability to move expands the ability of robots to perform more complex tasks. The basis of mobile robots is their navigation system. Such a system consists of various algorithms that ensure the fulfillment of tasks. Among these algorithms, it is worth highlighting: robot control when avoiding obstacles, finding a directional path, general robot motion control. These issues are considered in this paper.
Keywords: Control Algorithms; Mobile Robot; Navigation System; Robot Movement